The expression and dynamics of gender in newspaper journalism during the first twenty years of Lithuania’s independency - Sirtautienė, Daiva; Samulionytė, Virginija (Information & Media, 2015)
The problematics of gender relation in society is an area discussed in various aspects in the scientific world. The expression or the possibilities of expression of gender are actualized in various contexts of social life, and one of them is journalism. It should be noted that the latter, as an area of gender functioning, is multifaceted: on the one hand, it is equal rights in the labor market, the creation and presentation of journalistic production specialisation, on the other hand, it is the possibility to portray (in the broad sense) the view of genders, their relations in the texts, in this way sustaining or shaping particular notions.This article presents research, covering these aspects of the analysed object: the specialisation of topics as per gender and its dynamics in Lithuanian newspapers of different audience size, representing national, county and regional problems, and the shift of gender in the editorial offices of these newspapers.The aim of the research – to reveal the tendencies of gender expression and dynamics in Lithuanian newspapers’ journalism during the first twenty years of independent Lithuania (1991 and 2010 years).In pursuance of the aim, such objectives were set: to analyse the specialisation of topics and its dynamics as per gender; to investigate the quantity of different gender journalists during the studied periods; to discuss the shift of the amount of men and women journalists in the editorial offices. Applied methods: content analysis, comparison, cross-section, percentage analysis.The analysis of theme specialisation dominants of the national daily newspaper “Lietuvos žinios” in the aspect of gender in the researched periods (1991 y. and 2010 y.) shows that in the year 1991 men journalists wrote about such topics as politics, economics, history, culture, prepared reportages from the location of the events. Women journalists at the same time mostly concentrated on the culture topic, published reportages from the location of the events, presented publications on economics and politics, although, compared to men journalists, – relatively few. In the year 2010 the situation changed: the women started to lead in publishing articles on the topics of politics, law enforcement, and economics. The men journalists gave priority to sports and continued writing on cultural topics.The analysis of the 1991 y. publications of the daily newspaper “Vakarų ekspresas” shows that men journalists dominated in the topics of sports, economics, law enforcement, and education. Women at the same time mostly wrote about culture, exceptionally – about agriculture (this theme has not been recorded in 2010 y.) and the topics of the sea and journalism. In 2010 y. men journalists preferred sports, they led in the topic of politics, the topic of the sea. Culture continued to be the dominant theme of women journalists, they also wrote about current issues. The involvement of women journalists in the topic of health care increased, the attention given to the topics of economics and education became similar to men’s.In the regional newspaper “Banga” in 1991 y. men journalists mostly wrote about agriculture, environmental protection, history, law enforcement, and women journalists focused on politics, economics, education, current issues. In 2010 y. men journalists continued to lead in the topics of agriculture and sports, but all the other topics were mostly covered by women.It was established that the amount of women officially working in the editorial offices of the researched newspapers from 1991 to 2010 y. increased: in “Lietuvos žinios” – by a third, in “Vakarų ekspresas” and “Banga” – by a quarter.It was also observed that the amount of journalists working in the editorial office of “Lietuvos žinios” in 2010 y. increased in general, in “Vakarų ekspresas” – decreased, in “Banga” – remained similar. However, even under these circumstances, women became dominant in the composition of editorial offices.The amount of publications written by women also increased by a third in all three newspapers. The results of the survey suggest that in the journalist community of Lithuanian newspapers the process of feminization is apparent, which has influenced not only the changes in topic specialisation, but also the amount of publications.The fact that the amount of women journalists in all three editorial offices increased can be explained considering various circumstances. First, for several years the tendency to choose Journalism programme studies for women rather than men has been observed, e.g., in Klaipėda University, so naturally more women come to the labor market of journalism. If in the beginning of independency (1991 y.) the newspapers which portrayed the processes of change in the society, and were published in rather large print runs, were of high interest, in 2010 y. the demand for them decreased. This tendency was influenced not only by a variety of newspapers that emerged during the 19 years, stabilization of the society life, but also a novel form of virtual newspapers on the internet, accessible for the readers free of charge. It is likely that due to the latter reason the financial resources of publications decreased, directly influencing the journalists’ salary, which women are less demanding for as various publicly presented data portray. Considering the said circumstances it can be prognosed that the domination of women in the journalist community of Lithuanian newspapers should not alter hereafter.
Keywords: ...